Tweeting for Influence: Political Buzzers’ Speech Acts in 2024 Presidential Campaign - Soraya Soraya; Dinda Kholifa; Nadia Jufrisani (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2026)
During the presidential campaign, political posts of the buzzers is massive, particularly on digital platforms. However, research on the speech act of buzzers is limited. The present study focuses on investigating the content of political campaigns produced by the buzzers in the posts on X platform, the intention of the buzzers, and the effect of the posts on the audience. The research employed a qualitative approach and netnography. The study analyzed the content of three buzzer accounts, each of which represents one presidential candidate. In this case, the researchers become complete observers (lurking) in the cross-sectional study design. A total of 528 posts were collected manually during the campaign period. All content, which included text, images, videos, and emojis, was observed and noted. Then, the data were analyzed by speech act theory. The findings highlighted the power of the multimodal elements presented in the posts as the locutionary acts to strengthen the message impact and to increase credibility, specifically in attacking the opponents. The analysis of illocutionary acts revealed that the buzzers’ domination in assertive, directive, expressive, and the combination of speech acts.The perlocutionary effect of the posts was reflected in the audience engagement through likes and retweets. It can be concluded that the buzzers reach the possible voters through various means of information and strategy to mobilize them through claims, command, and emotion. The implication of the research provides insights that the audience should be aware that buzzers’ multimodal post to reach massive voters.